Real-World Study on Vedolizumab Serum Concentration, Efficacy, and Safety after the Transition from Intravenous to Subcutaneous Vedolizumab in Inflammatory Bowel Disease Patients: Single-Center Experience - Vlasta Oršić Frič; Vladimir Borzan; Ines Šahinović; Andrej Borzan; Sven Kurbel (MDPI AG, 2023)
Little is known about how the change from intravenous to subcutaneous vedolizumab in a real-life setting in inflammatory bowel disease patients on stable maintenance therapy affects clinical outcomes. We compared the data on vedolizumab serum trough concentration, efficacy, and safety prior to and six months after the switch from intravenous to subcutaneous vedolizumab. In total, 24 patients, 13 with ulcerative colitis (UC) and 11 with Crohn's disease (CD), were included. Mean serum trough concentration of intravenous vedolizumab was significantly lower than mean serum trough concentration of subcutaneous vedolizumab (p = 0.002). There was no significant difference between C-reactive protein levels, fecal calprotectin levels or clinical scores (Harvey-Bradshaw index or Partial Mayo score) prior to transition to subcutaneous vedolizumab and after 6 months. In four (16.7%) patients, two CD and two UC, therapy was discontinued during the follow-up period with a median of 5 months (minimum-maximum: 4-6). In all patients, therapy was discontinued due to loss of response. In total, 13 adverse events were reported by 11 patients, and the most common adverse event was COVID-19. No serious adverse events were reported. In conclusion, subcutaneous vedolizumab has shown to be effective and safe in patients on previously established maintenance therapy with intravenous vedolizumab.